2010
DOI: 10.1074/jbc.m109.059162
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Progressive Ca2+ Binding States of the Ca2+ Sensor Ca2+ Binding Domain 1 (CBD1) from the CALX Na+/Ca2+ Exchanger Reveal Incremental Conformational Transitions

Abstract: exchangers exhibit a common Ca 2ϩ -dependent regulatory mechanism, whereby their activity requires the presence of low concentrations of Ca 2ϩ on their intracellular surface, and their activity is augmented in parallel with elevated intracellular Ca 2ϩ levels (3). This important regulatory property may permit the timely coupling of exchange function to alterations in intracellular Ca 2ϩ concentrations to meet the continuous needs for overall Ca 2ϩ balance. The general similarities of exchange function and regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 27 publications
4
66
0
Order By: Relevance
“…6). Our findings are consistent with recent structural studies indicating that Ca 2ϩ binding enhances the stability of the Ca 2ϩ binding site of CBD1 near the hinge region while the overall structure of CBD1 remains largely unaffected (28). The underlying biological relevance is that the linker-dependent modification of Ca 2ϩ on/off kinetics at a specific regulatory site can diversify and widen the dynamic range of Ca 2ϩ sensing of CBD12 by nearly 2 orders of magnitude (while retaining a submicromolar range of Ca 2ϩ affinity).…”
Section: Discussionsupporting
confidence: 82%
“…6). Our findings are consistent with recent structural studies indicating that Ca 2ϩ binding enhances the stability of the Ca 2ϩ binding site of CBD1 near the hinge region while the overall structure of CBD1 remains largely unaffected (28). The underlying biological relevance is that the linker-dependent modification of Ca 2ϩ on/off kinetics at a specific regulatory site can diversify and widen the dynamic range of Ca 2ϩ sensing of CBD12 by nearly 2 orders of magnitude (while retaining a submicromolar range of Ca 2ϩ affinity).…”
Section: Discussionsupporting
confidence: 82%
“…However, this interpretation is unlikely, because although CBD1 was crystallized without G503 and upstream residues, the structure shows ion coordination identical to that of CBD12 for all CBD1's sites. 30,32 Moreover, G503 participates in the β-strand interactions of CBD2. 31 Finally, the G555P mutation in CALX-CBD12 (corresponding to G503P in this study) resulted in intact capacity but reduced affinity.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In spite of high sequence homology within the intracellular regions (Figure 1B), CALX exhibits a unique negative Ca 2+ regulatory property in contrast to the positive effect of other characterized NCXs (Hryshko et al, 1996). Our recent X-ray crystallographic analyses of individual CBD1 and CBD2 domains from the CALX 1.1 isoform showed that only CBD1 is a functional Ca 2+ binding domain ([Wu et al, 2010] and [Wu et al, 2009]). It has a nearly identical 4-Ca 2+ binding conformation to that of canine NCX1 (Nicoll et al, 2006), further supporting the importance of CBD1 in the Ca 2+ regulatory mechanism of NCXs.…”
Section: Introductionmentioning
confidence: 99%
“…However, Ca 2+ interaction with CBD1 from CALX or NCX1 results in a protein conformational change limited to the local Ca 2+ binding site, mainly the 1E-1F loop of CBD1 (the loop between the β strands 1E and 1F), arguing overall protein conformational change is not required for the Ca 2+ regulation ([Wu et al, 2010] and [Johnson et al, 2006]). NCXs have a very short linker predicted between CBD1 and CBD2 (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%